2023
DOI: 10.3390/math11040814
|View full text |Cite
|
Sign up to set email alerts
|

Are State-Owned Enterprises Equally Reliable Information Suppliers? An Examination of the Impacts of State Ownership on Earnings Management Strategies of Chinese Enterprises

Abstract: Earnings management refers to a company’s use of either accounting techniques (accrual-based earnings management) or real economic activities (real earnings management) to manipulate reported earnings and mislead users of financial information. It often indicates serious ethical issues in a company’s management, which will affect the reliability and sustainability of a firm’s services in the supply chain. Using A-share listed Chinese firms on the Shanghai and Shenzhen Stock Exchanges, we investigated the impac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 41 publications
(104 reference statements)
0
2
0
Order By: Relevance
“…For example, Lu using 11,905 A-share listed Chinese firm-year observations on the Shanghai and Shenzhen Stock Exchanges, investigated effects of State ownership on management's decision to select REM/AEM earnings management strategies. Authors found that state-owned enterprises tend to favor REM over AEM earnings management strategies more than private [10]. However, SOEs could have different level of government engagement, and privatized SOEs might look more similar to POEs instead.…”
Section: Literature Reviewmentioning
confidence: 99%
“…For example, Lu using 11,905 A-share listed Chinese firm-year observations on the Shanghai and Shenzhen Stock Exchanges, investigated effects of State ownership on management's decision to select REM/AEM earnings management strategies. Authors found that state-owned enterprises tend to favor REM over AEM earnings management strategies more than private [10]. However, SOEs could have different level of government engagement, and privatized SOEs might look more similar to POEs instead.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Contemporaneous studies on Earnings management and ownership structure (Lu et al, 2023) using A-share listed Chinese firms on both the Shanghai and Shenzhen Stock Exchanges, investigated impacts of State ownership on management's decision to select REM or AEM earnings management strategies. Authors found that state-owned enterprises tend to favor REM over AEM earnings management strategies more than private.…”
Section: Literature Reviewmentioning
confidence: 99%